MENJAGA TRADISI WALISONGO:: Urgensi Moderasi Beragama bagi Penguatan Kajian Kebangsaan, Keberagamaan dan Tradisi Lokal Bagi Mahasiswa Perguruan Tinggi - Kurnia Muhajarah (LPPM IAIN Sultan Amai Gorontalo, 2022)
Abstract: The visions of some groups about nationality, diversity and local traditions always confront each other as if they are contradictory and impossible to reconcile. The concept of citizenship does not conform to Islamic teachings, especially to local traditions, because the regulation of human life is not in the hands of the national state, but in the hands of the Islamic state. This article aims to explore the urgency of Islamic moderation in higher education to strengthen national, religious and local traditions. This study uses a descriptive qualitative method and a literature review. Using this method, it is expected that researchers can comprehensively analyze the importance of Islamic moderation in higher education using national, religious and local traditions. These triangles are interconnected and mutually reinforcing. This is the reality of human civilization, recognized in Islamic teachings as part of God's will in creating heterogeneous people. Students should be taught Islamic moderation so that their religious views and attitudes reflect national values. Based on the results of the investigation, it was found that many things were national, religious and local traditions that do not conflict with Islam; and the need to integrate the subject of Islam and religious moderation with other courses.